The political economy of the Abe government and Abenomics reforms - Hoshi, Takeo; Lipscy, Phillip Y. (Cambridge University Press, 2021)
This volume seeks to explain the political economy of the Abe government and the so-called 'Abenomics' economic policies. The Abe government represents a major turning point in postwar Japanese political economy. In 2019, Abe became the longest serving Prime Minister in Japanese history. Abe's government stood out not only for its longevity, but also for its policies. Abe came to power promising to reinvigorate Japan's economy under the banner of Abenomics. He pursed a host of structural reforms and industrial promotions to increase Japan's potential growth rate. Abe also achieved important legislative victories in security policy. However, the government also faced significant controversies. The book will hold appeal to scholars and students specializing in the study of Japanese politics, comparative political economy, the politics of contemporary advanced democracies, macroeconomic policy, labor market reforms, corporate governance, gender equality, agricultural reforms, energy and climate change, and East Asian security.